Revised magnetostratigraphy and characteristics of the fluviolacustrine sedimentation of the Kashmir basin, India, during Pliocene‐Pleistocene - Basavaiah, N.; Appel, E.; Lakshmi, B.V.; Deenadayalan, K.; Satyanarayana, K.V.V.; Misra, Saumitra; Juyal, N.; Malik, M.A. (My University, 2010)
The Pliocene‐Pleistocene Karewa Group sediments of the Kashmir basin, India, provide an important continental archive for past climatic reconstruction. The present study reevaluates the magnetic polarity stratigraphy and the nature of the depositional environment at a 440‐m‐thick section along Romushi river near Pakharpur (33°48′50″N, 74°45′54″E). Magnetic remanences are predominantly carried by Ti‐rich titanomagnetite and magnetite. We identified eight normal and eight reversed‐polarity magnetozones in this succession, ranging between 4.40 and 0.77 Ma. The polarity sequence includes the new identification of the Cochiti and the Mammoth and their preceding and succeeding reversed/normal as well as the Jaramillo subchrons. Anisotropy of magnetic susceptibility data suggest the existence of northeast‐ and northwest‐flowing fluvial system before 4.18 Ma, indicating the Pir Panjal range at the southwest as the sediment source area. Following this, the valley was under the influence of fluviolacustrine environment between 4.18 and 0.77 Ma. Our results suggest relatively strong flow velocity toward the northeast during the upper Gilbert, Gauss, and lower and middle Matuyama chrons (4.18–1.07 Ma). In the upper Matuyama chron (<1.07 Ma), the prevailing paleocurrent direction in the basin changed toward the northwest with a reduced flow velocity, indicating the emergence of the ancestral Jhelum river. On the basis of the magnetic polarity chronology, the sediment accumulation rate indicates a very low value of ∼4.6 cm kyr−1 before 1.95 Ma to ∼33 cm kyr−1 between 1.95 and 1.77 Ma and 23 cm kyr−1 after 1.77 Ma. We attribute temporal changes in sedimentation rate to the interplay between climate (predominantly westerlies) and tectonics (pulsating Pir Panjal uplift).
Keywords: Magnetostratigraphy; fluviolacustrine sedimentation; Pleistocene; Pliocene; Kashmir Basin